Aplikasi Kapur Kalsit pada Tanah Gambut untuk Meningkatkan pH Air Media Pemeliharaan Ikan Patin - Olivia Riana Sari; Dade Jubaedah; Marini Wijayanti; Marsi Marsi (Seminar Nasional Lahan Suboptimal, 2021)
Sari OR, Jubaedah D, Wijayanti M, Marsi M. 2021. Application calcite limein peat soil to improve water pH in culture media of catfish (Pangasius sp.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 844-853.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Application of calcite lime has been researched to be able to increase the pH of water and soil of catfish culture media. Application of lime is not only affected by soil and water pH but also affected by organic matter as in peat soil that have high carbon organic.  This research aims to know the effect of calcite lime and various C-organic on water and soil pH for culture of catfish.This research was conducted from July to December 2019 at the Laboratory of Aquaculture Experimental Pond, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University. This research use Factorial Completely Randomized Design. Thefirst factor is different dose of calcite lime that are 7000 kg/ha equivalent CaO (K1), 8000 kg/ha equivalent CaO (K2), 9000 kg/ha equivalent CaO (K3), 10000 kg/ha equivalent CaO (K4). The second factor is peat soil with different soil organic carbon that are 19.72% (C1) and 59.98% (C2). The results of this study indicated that K3C1(interaction of dosage of lime 9000 kg/ha equivalent to CaO and 19.62% C-organic) increased the initial soil pH from 3.2 to 7.43, and water pH from 3,2 to 7.33, and produces 100% survival of catfish, absolute growth of length 9.08cm and absolute growth of weight 4.60 g.